JONES. Mark William (2023) 1923. The Crisis of German Democracy in the Year of Hitler’s Putsch: New York, Basic Books, 432 págs. - Morello, Juan (Cuadernos del Ciesal, 2025)
Reseña de JONES. Mark William (2023) 1923. The Crisis of German Democracy in the Year of Hitler's Putsch, New York, Basic Books.